Recycling of waste tire fibers into advanced aerogels for thermal insulation and sound absorption applications. Issue 5 (October 2020) - Thai, Quoc Ba; Chong, Ren Ooi; Nguyen, Phuc T.T.; Le, Duyen K.; Le, Phung K.; Phan-Thien, Nhan; Duong, Hai M.
Graphical abstract: Highlights: Advanced fabrication of rubber aerogel via a cost effective and time saving method. Rubber aerogel has an ultra-low density and a high porosity properties. Rubber aerogel has a robust mechanical properties with the Young's modulus. Rubber aerogel can be a potential material for thermal insulation applications. Rubber aerogel can be a potential material for sound absorption applications. Abstract: According to the European Waste Codes EWC 19.12.08, fibers from used tires are known as special wastes that must be burned or buried. However, these activities would pose additional risks including soil pollution, and groundwater contamination. Scientists are continually discovering more new ways to recycle these wastes in order to minimize their ecological consequences. Our effort has been also directed into this direction, and we have been able to convert rubber fibers from tire waste into aerogels, an ideal candidate for a wide range of advanced applications due to their low density, high porosity, low thermal conductivity and high sound absorption coefficient. A novel but simple and time-saving strategy to fabricate rubber aerogel from waste tire fibers, derived from car tire wastes, is reported using a freeze-drying process. The obtained rubber aerogel with a robust mechanical performance, exhibiting a Young's modulus up to 965.6 kPa and density 91 mg cm −3, can withstand a large elastic deformation without fracture. In addition, with a highly porous structure (porosity > 90 %) and an ultralight light density (20−91 mg cm −3 ), our rubber aerogels have a high sound absorption efficiency (noise reduction coefficient, or NRC of 0.56), and a low thermal conductivity (0.035−0.049 W m -1 K -1 ). These advanced rubber aerogels can be a promising candidate for thermal and acoustic insulation in cabins, vehicles, buildings, and aerospace.